2019
DOI: 10.1186/s13019-019-0933-8
|View full text |Cite
|
Sign up to set email alerts
|

The experience of transcatheter closure of postoperative ventricular septal defect after total correction

Abstract: Background The purpose of this study was to describe our experience with patients who underwent transcatheter closure of a post-operative ventricular septal defect (VSD). Methods All patients who underwent transcatheter closure of a VSD after total correction of congenital heart disease since 2012 were enrolled. Medical records were retrospectively reviewed to determine the patients’ initial diagnosis, closure device used, and final outcome after device closure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Even so, other studies have shown that the patient's weight that can be done with a transcatheter defect closure is at least 7 kg and even 6 kg. 16,17 This is because body weight is one of the factors that contribute to the successful closure of defects with transcatheter occlusions because patients with low body weight have small vascular diameters so that the selection of the right device and vascular access becomes more difficult. 18 The most common type of VSD that was closed with a transcatheter in this study was the perimembranous type, followed by the subaortic type and the SADC type.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, other studies have shown that the patient's weight that can be done with a transcatheter defect closure is at least 7 kg and even 6 kg. 16,17 This is because body weight is one of the factors that contribute to the successful closure of defects with transcatheter occlusions because patients with low body weight have small vascular diameters so that the selection of the right device and vascular access becomes more difficult. 18 The most common type of VSD that was closed with a transcatheter in this study was the perimembranous type, followed by the subaortic type and the SADC type.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to reoperation, the endovascular approach decreased recovery time and cost, while avoiding the high surgical risk associated with recent sternotomy. The long-term risks and durability of percutaneous LV-CS fistula closure are unknown, although procedures following a similar technique for ventricular septal defect (VSD) occlusion have demonstrated favorable efficacy, procedural safety, and short-term clinical outcomes ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the surgery is simpler, with a shorter time as well as less mechanical damage and intraoperative blood loss. 6,19 soft and elastic design of Amplatzer duct occluder II reduces surgical complications According to Santhanam et al, 32 the most common complication during VSD occlusion is RS (pooled rate, 15.9%; 95% CI, 10.9%-21.5%). Other complications included arrhythmia (pooled rate, 10.3%; 95% CI, 8.3%-12.4%) and valve dysfunction (pooled rate, 4.1%; 95% CI, 2.4%-6.1%), and the incidence of cAVB was 1.1% (95% CI, 0.5%-1.9%).…”
Section: Es (95% Ci)mentioning
confidence: 99%
“…5 Recently, the off -label use of the ADO II for closing VSD has been described. 6 Due to the finer and more flexible mesh structure of the ADO II, the device can pass through a small 4F or 5F catheter system. 7 In addition, its soft design is expected to reduce the risk of cAVB.…”
mentioning
confidence: 99%